Absence of myofibrillar myopathy in Quarter Horses with a histopathological diagnosis of type 2 polysaccharide storage myopathy and lack of association with commercial genetic tests. (1st April 2022) - Valberg, Stephanie J.; Henry, Marisa L.; Herrick, Keely L.; Velez‐Irizarry, Deborah; Finno, Carrie J.; Petersen, Jessica L.
Abstract: Background: Genetic tests for variants in MYOT (P2; rs1138656462), FLNC (P3a; rs1139799323 or P3b; rs1142918816) and MYOZ3 (P4; rs1142544043) genes are offered commercially to diagnose myofibrillar myopathy (MFM) and type 2 polysaccharide storage myopathy (PSSM2) in Quarter Horses (QH). Objectives: To determine if PSSM2‐QH has histopathological features of MFM. To compare genotype and allele frequencies of variants P2, P3, P4 between control‐QH and PSSM2‐QH diagnosed by histopathology. Study design: Retrospective cross‐sectional. Methods: The study includes a total of 229 healthy control‐QH, 163 PSSM2‐QH GYS1 mutation negative. Desmin stains of gluteal/semimembranosus muscle were evaluated. Purported disease alleles P2, P3a, P3b, P4 were genotyped by pyrosequencing. Genotype, allele frequency and total number of variant alleles or loci were compared between phenotypes using additive/genotypic and dominant models and quantitative effects evaluated by multivariable logistic regression. Results: Histopathological features of MFM were absent in all QH. A P variant allele at any locus was not associated ( P > .05) with a histopathological diagnosis of PSSM2 and one or more P variants were common in control‐QH (57%) and PSSM2‐QH (61%). Allele frequencies (control/PSSM2) were: 0.24/0.21 (P2), 0.07/0.12 (P3a), 0.07/0.11 (P3b) and 0.06/0.08 (P4). P3a and P3b loci were not independent ( r 2 = 0.894); and not associated with PSSM2 histopathology comparing the haplotype of both P3a and P3b variants to other haplotypes. A receiver operator curve did not accurately predict the PSSM2 phenotype (AUC = 0.67, 95% CI 0.62‐0.72), and there was no difference in the total number of variant loci or total variant allele count between control‐QH and PSSM2‐QH. Main limitations: P3a and P3b were not in complete linkage disequilibrium. Conclusions: The P2, P3 and P4 variants in genes associated with human MFM were not associated with PSSM2 in 392 QH. Their use would improperly diagnose PSSM2/MFM in 57% of healthy QH and fail to diagnose PSSM2 in 40% of QH with histopathological evidence of PSSM2. Resumo: Contexto: Testes genéticos para detecção das mutações MYOT (P2; rs1138656462), FLNC (P3a; rs1139799323 ou P3b; rs1142918816) e MYOZ3 (P4; rs1142544043) são oferecidos comercialmente para diagnosticar miopatia miofibrilar (MMF) e miopatia por acúmulo de polissacarídeo tipo 2 (PSSM2) em cavalos Quarto de Milha (QM). Hipóteses/Objetivos: Determinar se PSSM2‐QM tem características similares à MMF. Comparar o genótipo e a frequência dos alelos variantes P2, P3, e P4 entre cavalos QM controle, e PSSM2‐QM diagnosticados por histologia. Métodos: 229 cavalos QH saudáveis como controle, e 163 PSSM2‐QM positivos na histologia e negativos para a mutação GYS1. Metodologia: Amostras dos músculos glúteo/semimembranoso foram avaliadas após coloração com desmina. Os pretensos genes alelos P2, P3a, P3b e P4 foram genotipados por pirosequenciamento. Genótipo, frequência alélica, e número total de variância alélica ou loci foram comparados entre os fenótipos usado aditivo/genotípico e modelos dominantes e efeitos quantitativos através de regressão logística multivariável. Resultados: Características histopatológicas de MMF não foram encontradas em nenhum QM. Uma variante alélica P em qualquer uma dos loci não foi associada ( P > .05) com o diagnóstico histopatológicos de PSSM2 e uma ou mais variante P foram comuns em QM controles (57%) e PSSM2‐QM (61%). Frequência alélica (controle/PSSM2) foram: 0.24/0.21 (P2), 0.07/0.12 (P3a), 0.07/0.11 (P3b), e 0.06/0.08 (P4). P3a e P3b loci não foram independentes ( r 2 = 0.894); e não foram associados com achados histopatológicos de PSSM quando comparando o haplótipo de ambas as variantes P3a e P3b com os outros haplótipos. A curva característica de operação do receptor não previu acuradamente o fenótipo PSSM2 (AUC = 0.67, 95% IC 0.62‐0.72), e não houve diferença no número dotal de variantes no loci ou na contagem de variantes alélicas total entre QM controles e PSSM2‐QM. Principais limitações: P3a e P3b não estavam em desequilíbrio de ligação. Conclusões: As variantes P2, P3 e P4 em genes associados com MMF em humanos não foram associadas com PSSM em 392 QM. O seu uso diagnosticaria impropriamente PSSM2 e MMF em 57% dos cavalos saudáveis utilizados como controle e não diagnosticaria PSSM2 em 40% dos QM com evidência histológica de PSSM2.